Gold(I) selenium N-heterocyclic carbene complexes as potent antibacterial agents against multidrug-resistant gram-negative bacteria via inhibiting thioredoxin reductase - Xiuli Chen; Shibo Sun; Sheng Huang; Han Yang; Qing Ye; Lin Lv; Yanshan Liang; Jinjun Shan; Jianqiang Xu; Wukun Liu; Tonghui Ma (Redox Biology, 2023)
Multidrug-resistant (MDR) Gram-negative bacteria have become a global threat to human life and health, and novel antibiotics are urgently needed. The thioredoxin (Trx) system can be used as an antibacterial target to combat MDR bacteria. Here, we found that two active gold(I) selenium N-heterocyclic carbene complexes H7 and H8 show more promising antibacterial effects against MDR bacteria than auranofin. Both H7 and H8 irreversibly inhibit the bacterial TrxR activity via targeting the redox-active motif, abolishing the capacity of TrxR to quench reactive oxygen species (ROS) and finally leading to oxidative stress. The increased cellular superoxide radical levels impact a variety of functions necessary for bacterial survival, such as cellular redox balance, cell membrane integrity, amino acid metabolism, and lipid peroxidation. In vivo data present much better antibacterial activity of H7 and H8 than auranofin, promoting the wound healing and prolonging the survival time of Carbapenem-resistant Acinetobacter baumannii (CRAB) induced peritonitis. Most notably in this study, we revealed the influence of gold(I) complexes on both the Trx system and the cellular metabolic states to better understand their killing mechanism and to support further antibacterial drug design.